Pelatihan Pemanfaatan Gawai dan Perhitungan Keuangan Usaha dalam Menumbuhkan Jiwa Kewirausahaan pada Siswa SMK - Irmeilyana, Irmeilyana; Ngudiantoro, Ngudiantoro; Maiyanti, Sri Indra; Setiawan, Arum; Zubaidah, Zubaidah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The entrepreneurial spirit is one of the basics for forming the competencies of vocational school graduates. The lack or absence of ideas and enthusiasm (mental) for vocational school students to become entrepreneurs can be due to their mindset and skills (competencies) which are still lacking. The area of activity carried out is increasing the knowledge, skills and entrepreneurial spirit of students at SMK Negeri 1 Tanjung Batu, Ogan Ilir Regency, South Sumatra, through training in using gadgets, mastering digital literacy and using social media in digital marketing, as well as improving management skills. finance (including administration) through the use of Excel. This community service activity (PPM) also introduced several examples of business ideas and provides practical simulations of business simulations carried out by students participating in the Mathematics Entrepreneurship Course I in the current semester at the same time as PPM activity. Methods for implementing activities include presentations (material transfer), questions and answers and discussions, demonstrations/practices, simulations, and implementation assistance. Training on using smartphones to create creative content on social media can increase the enthusiasm of vocational school students majoring in TKJ (Department of Computer and Network Engineering) in getting to know the world of business, so that they can also develop their entrepreneurial spirit and become more familiar with business ideas. Apart from that, students become more familiar with using Microsoft Excel for simple calculations on business financial bookkeeping problems, so that it can motivate them to further improve their competency in using devices. The involvement of students as assistants in implementing the PPM activities of the Village Lecture Scheme is a field practice from the Mathematics Entrepreneurship Course I (in the MBKM curriculum), so that they can gain experience, information and contribute to the community outside the campus, as well as business experience.